2015
DOI: 10.1289/ehp.1307922
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Environmental Exposures and Exacerbation of Asthma: An Update to the 2000 Review by the Institute of Medicine

Abstract: Background: Previous research has found relationships between specific indoor environmental exposures and exacerbation of asthma.Objectives: In this review we provide an updated summary of knowledge from the scientific literature on indoor exposures and exacerbation of asthma.Methods: Peer-reviewed articles published from 2000 to 2013 on indoor exposures and exacerbation of asthma were identified through PubMed, from reference lists, and from authors’ files. Articles that focused on modifiable indoor exposures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
257
4
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 353 publications
(293 citation statements)
references
References 112 publications
9
257
4
6
Order By: Relevance
“…Relatedly, indoor endotoxin exposure is also a strong risk factor for asthma exacerbation (35). Although the TREM1 gene itself was not differentially expressed in our data, the body of transcriptomic evidence presented here implicates increased TREM-1 signaling as a potential early molecular indicator of worsening asthma control.…”
Section: Discussionmentioning
confidence: 49%
“…Relatedly, indoor endotoxin exposure is also a strong risk factor for asthma exacerbation (35). Although the TREM1 gene itself was not differentially expressed in our data, the body of transcriptomic evidence presented here implicates increased TREM-1 signaling as a potential early molecular indicator of worsening asthma control.…”
Section: Discussionmentioning
confidence: 49%
“…Se ha demostrado que la exposición persistente a alérgenos a los cuales el paciente está sensibilizado, tales como ácaros del polvo, caspa de gato, caspa de perro y cucaracha, aumentan los sínto-mas y las exacerbaciones de asma 37 . lo anterior es especialmente relevante cuando además se asocia una infección viral 38 .…”
Section: Alérgenosunclassified
“…Se ha demostrado que la exposición crónica al humo del cigarrillo se asocia a un aumento de las exacerbaciones de asma y por otro lado la exposición pasiva o activa al humo de cigarrillo en pacientes con asma puede causar resistencia al tratamiento con corticoides inhalados 37 . De esta manera la exposición a este contaminante es un factor muy importante a evaluar en pacientes con asma severo problemático 38 .…”
Section: Humo De Cigarrillounclassified
See 1 more Smart Citation
“…[3][4][5][6][7] Until now, the causal agents and the mechanisms behind the association between moisture damage and the adverse health effects are not well known. It has been suggested that microbial components such as cell fragments or spores shed during fungal growth in moisture-damaged buildings may induce inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%